The Importance of Entrepreneurship Education from an Early Age - Prasakti, Angga Warda; Idrus, Ali (Mitra Palupi, 2024)
Background: It is important to give children the opportunity to learn entrepreneurship early on so that they have the knowledge and skills needed. Therefore, parents and educators need to understand their children's interests and talents before deciding whether they should learn entrepreneurship early on. Purpose: This research aims to provide an understanding and overview of the importance of delivering entrepreneurship education from an early age, as well as recommendations for methods that are worth trying and using in early childhood education. Design and methods: Qualitative research is used. The data collection technique that researchers use is the literature review method to examine the topics raised. Results: The importance of improving the quality of entrepreneurship among the younger generation as one of the efforts to advance the economy and create jobs. This can be done through various means, such as the provision of training, curriculum development, and increased accessibility to resources and information on entrepreneurship. Other factors, such as providing encouragement and motivation to young people to take risks and develop creative ideas, are also important steps in creating a young generation that is a driving force in economic progress.